2010
DOI: 10.1200/jco.2009.24.6611
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor Receptor 1 (IGF1R) Gene Copy Number Is Associated With Survival in Operable Non–Small-Cell Lung Cancer: A Comparison Between IGF1R Fluorescent In Situ Hybridization, Protein Expression, and mRNA Expression

Abstract: PurposeThe purpose of this study was to characterize insulin-like growth factor-1 receptor (IGF1R) protein expression, mRNA expression, and gene copy number in surgically resected non–small-cell lung cancers (NSCLC) in relation to epidermal growth factor receptor (EGFR) protein expression, patient characteristics, and prognosis.Patients and MethodsOne hundred eighty-nine patients with NSCLC who underwent curative pulmonary resection were studied (median follow-up, 5.3 years). IGF1R protein expression was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
101
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 26 publications
(5 reference statements)
21
101
2
Order By: Relevance
“…In a retrospective study, Cappuzzo et al reported that 76.4% surgically resected NSCLC were positive IGF-1R expression (Cappuzzo et al, 2010). Dziadziuszko's group reported 84% NSCLC samples showed IGF-1R immunopositive staining (Dziadziuszko et al, 2010). They also demonstrated the high level IGF-1R expression was significantly associated with squamous cell histology and late stage.…”
Section: Discussionmentioning
confidence: 91%
“…In a retrospective study, Cappuzzo et al reported that 76.4% surgically resected NSCLC were positive IGF-1R expression (Cappuzzo et al, 2010). Dziadziuszko's group reported 84% NSCLC samples showed IGF-1R immunopositive staining (Dziadziuszko et al, 2010). They also demonstrated the high level IGF-1R expression was significantly associated with squamous cell histology and late stage.…”
Section: Discussionmentioning
confidence: 91%
“…Dziadziuszko et al (17) found that IGF-1R expression was higher in squamous cell carcinomas than in other histological types and was associated with disease stage. Cappuzzo et al (18) reported that a positive IGF-1R expression was significantly associated with squamous cell histology and grade III differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In stage I disease, high IGF-1R expression was associated with significantly shorter survival than low IGF-1R expression. Dziadziuszko et al (17) evaluated 189 NSCLCs and showed that the IGF-1R gene copy number is of prognostic value; nonetheless, IGF-1R protein expression upon immunohistochemical analysis was not related to survival. Ludovini et al (19) reported that IGF-1R protein expression alone was not significantly associated with survival, although high co-expression of both IGF-1R and epidermal growth factor receptor was associated with shorter Table IV.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on cancer have revealed that the lack of correlation between mRNA and protein levels can be attributed to mRNA translational silencing, cleavage, or alternative splicing (Dziadziuszko et al 2010, Mountzios et al 2013. In the IGF1R context, alternative mRNA splicing can lead to distinct protein degradation rates in cancer cells (Mountzios et al 2013) while the frequently expressed isoform (alpha) of IGF1R is not directly associated with global IGF1R gene expression (Pollak 2012).…”
Section: Discussionmentioning
confidence: 99%